Improving access to services in neuro-developmental disability: proceedings of a national meeting to advance community capacity - David B. Nicholas; Lucyna M. Lach; Samantha B. Sutherland; Joanne Maxwell; Stephanie McFarland; Anton R. Miller; Angela Clancy; Julie Scorah (BMC Proceedings)
Abstract As part of a participatory project to advance navigational service delivery systems for children with neurodevelopmental disability (NDD) and their families, this paper addresses proceedings from a capacity-building conference in Vancouver, Canada. A total of 29 invited key stakeholders attended the meeting with the following aims: knowledge sharing amongst provincial/territorial regions advancing NDD navigation capacity; sustainable action-oriented knowledge exchange; and operationalizing next steps to build navigation resources across Canadian regions. Regional representation included multiple and inter-sectoral partners (e.g., not-for-profit organizations, government, education, health, researchers, etc.) strategically invited to address mutually-agreed upon regional challenges, where ideas for envisioning, planning and success could be developed for ultimate operationalization in three Canadian provinces and one territory based on need for building navigational service delivery systems in NDD. Advancements in navigational service delivery were shared by site leads in the four represented regions of the initiative: Alberta, British Columbia, Quebec, and Yukon. Each regional lead conveyed targeted accomplishments, priorities and issues in moving navigation forward. Identified successes comprised the development of trusting partnerships across agencies and sectors, innovation and connection among service/navigation organizations and leaders, and training advances. Struggles included insufficient regional clarity on guiding principles for navigation services, a lack of resources relative to family need for services, and insufficient infrastructural supports in regions. Based on key learnings within and across regional groups, plans for regional development were strategized and shared.